Decomposing Gender Wage Gaps - A Family Economics Perspective - Dorothée Averkamp; Christian Bredemeier; Falko Juessen (ZBW - Leibniz Information Centre for Economics, 2021)
We show that parts of the unexplained wage gap in standard Oaxaca-Blinder decompositions result from the neglect of the role played by the family for individual wages. We present a simple model of dual-earner households facing a trade-off regarding whose career to promote and show analytically that the standard Oaxaca-Blinder approach overestimates the degree of pay discrimination. Unbiased decompositions can be obtained when the Oaxaca-Blinder wage equation is augmented by the characteristics of the individual's partner. In an empirical application, we find that this extended decomposition explains considerably larger shares of the gender wage gap than does the standard decomposition.
Keywords: J31; J16; J12; J71; J24; 330; Gender wage gap; Oaxaca-Blinder; dual-earner households; discrimination